Manajemen Kerja Tim Perpustakaan dalam Meningkatkan Mutu Pendidikan - Arif, Ahmad; Jamilus, Jamilus (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
A library or book or book is a collection of paper or similar material containing written or printed results, bound into one material so that it is easy to read and totaling at least 48 pages. The term library then gets a prefix to become a library. Library means (a) a place, building, space provided for maintaining and using a collection of books, and so on, (b) a collection of books, magazines and other library materials that are stored for reading, study and discussion. other derivative terms such as: library materials, librarian, librarianship, and science. Library management is an effort to achieve goals by utilizing human resources, information, systems and sources of funds while taking into account management functions, roles and expertise. In order to achieve the goal, human and non-human resources are needed in the form of financial, technical, physical, equipment, natural, information, ideas, regulations and technology resources. These resources are managed through a management process that includes planning, organizing, leading and supervising the expected and dispensing of services. This study uses a qualitative approach to the type of library research. Library research or library research aims to collect data and information sourced from books, scientific articles, magazines, documents, notes, and historical stories as well as other stories contained in the library room. Changes and developments in the times have positive and negative impacts that consciously change human functions and are replaced by technology. Technological changes occur in all joints and areas of life, including Islamic educational institutions. This attracts the attention of stakeholders in the field of Islamic education in determining policy directions, innovating, developing contemporary educational curricula and media and changing conventional education patterns by synergizing with changes in the current era. Changes - changes in the context of improving service quality need to be considered to answer customer requests in this case students and parents of students and be able to print quality output and improve the quality of education in Islamic educational institutions. Keywords: Library Team Work In Improving Quality